Mutual Conservation of Redox Mediator and Singlet Oxygen Quencher in Lithium-Oxygen Batteries - Kwak, Won-Jin; Freunberger, Stefan A.; Kim, Hun; Park, Jiwon; Trung Thien Nguyen; Jung, Hun-Gi; Byon, Hye Ryung; Sun, Yang-Kook (AMER CHEMICAL SOC, 2019)
Li-O-2 batteries are plagued by side reactions that cause poor rechargeability and efficiency. These reactions were recently revealed to be predominantly caused by singlet oxygen, which can be neutralized by chemical traps or physical quenchers. However, traps are irreversibly consumed and thus only active for a limited time, and so far identified quenchers lack oxidative stability to be suitable for typically required recharge potentials. Thus, reducing the charge potential within the stability limit of the quencher and/or finding more stable quenchers is required. Here, we show that dimethylphenazine as a redox mediator decreases the charge potential well within the stability limit of the quencher 1,4-diazabicyclo[2.2.2]octane. The quencher can thus mitigate the parasitic reactions without being oxidatively decomposed. At the same time the quencher protects the redox mediator from singlet oxygen attack. The mutual conservation of the redox mediator and the quencher is rational for stable and effective Li-O-2 batteries.
Keywords: LI-O-2 BATTERIES; SUPEROXIDE ANION; SOLID-ELECTROLYTE; STABILITY; RECHARGEABILITY; DISMUTATION; LIMITATIONS; GENERATION; DISCHARGE; CELLS